2022
DOI: 10.1002/14651858.cd014384.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic dose reduction compared to dose continuation for people with schizophrenia

Abstract: Background Antipsychotic drugs are the mainstay treatment for schizophrenia, yet they are associated with diverse and potentially dose‐related side effects which can reduce quality of life. For this reason, the lowest possible doses of antipsychotics are generally recommended, but higher doses are often used in clinical practice. It is still unclear if and how antipsychotic doses could be reduced safely in order to minimise the adverse‐effect burden without increasing the risk of relapse. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 218 publications
1
9
0
Order By: Relevance
“…4 Individuals with schizophrenia and their clinicians can choose an antipsychotic based on not only the tolerability profile but also the formulation. 3 Unanswered is the place in therapy of antipsychotic transdermal delivery systems as an alternative to both orally administered antipsychotic medication and their long-acting injectable formulations. 4 All-cause discontinuation (ACD) is an important acceptability outcome in double-blind, randomized, placebo-controlled trials for schizophrenia drugs and can serve as a proxy measure for overall effectiveness.…”
Section: Clinical Neurosciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Individuals with schizophrenia and their clinicians can choose an antipsychotic based on not only the tolerability profile but also the formulation. 3 Unanswered is the place in therapy of antipsychotic transdermal delivery systems as an alternative to both orally administered antipsychotic medication and their long-acting injectable formulations. 4 All-cause discontinuation (ACD) is an important acceptability outcome in double-blind, randomized, placebo-controlled trials for schizophrenia drugs and can serve as a proxy measure for overall effectiveness.…”
Section: Clinical Neurosciencesmentioning
confidence: 99%
“…2 For other antipsychotics, meta-analyses of randomized controlled trials have demonstrated that dose reduction increases the risk of relapse. 3,4 However, no study, to our knowledge, has examined the effect of clozapine dose reduction on relapse.…”
mentioning
confidence: 99%
“…Most studies examining low-dose treatment were performed in chronic patients, or nonselected patients, who were often treated with antipsychotics for many years (Rodolico et al, 2022). Of the 25 studies selected by Rodolico et al in their recent Cochrane review of dose-reduction studies, all but one were either in chronic patients (nine studies) or in patients whose course characteristics were not specified (15 studies).…”
Section: Dose Reduction and Relapse Riskmentioning
confidence: 99%
“…The abrupt dose-reduction schemes and the rather long-term treatment with antipsychotics of most patients included in the review probably add to the likelihood of rebound psychoses. Nevertheless, the figures on relapse rates are reassuring: “Dose reduction in comparison to continuation may increase the risk of rehospitalization based on data from eight studies with estimable effect sizes; however, the 95% confidence interval included the possibility of no difference, amounting to very low certainty evidence.” Similarly, in data from 20 studies, dose reduction increased the risk of relapse twofold, but this was limited to low-certainty evidence too (Rodolico et al, 2022).…”
Section: Dose Reduction and Relapse Riskmentioning
confidence: 99%
“…Even though a meta-analysis suggested that the risk of relapse in patients undergoing dose reduction is twofold of their maintenance counterparts, neurocognitive functioning in the former is significantly improved after dose reduction [23]. A recent systematic review reported similar findings and called for more attention to this approach concerning its potential to improve patients’ quality of life and global functioning [24].…”
Section: Introductionmentioning
confidence: 99%